Komunikasi dan Pembangunan Partisipatif - Rini Rinawati (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2006)
A participatory development philosophy has shifted the traditional linear development. Through the new development principles, hopefully, members of village might actively participate in development process. The program called Community Action Plan (CAP) based on community participation releases document such as Mid-term Development Plan on the level of village. Communication system is needed to help people transforming their goals, values, and cultural beliefs into the plan.